The importance of education for economic growth in ASEAN - Othman, Kamarudin; Ahmad Fuad, Hanani; Omar, Hapiza; Bidin, Samsiah (GADING Journal for the Social Sciences, 2024)
Education is a crucial factor in ensuring economic growth, particularly in emerging and developing countries. However, according to the World Bank (2019), only 59% of potential productivity growth was attributed to human capital investment in ASEAN, suggesting that such investment does not significantly impact growth. This study, therefore, examined the role of education in economic development across the ASEAN region, including Malaysia, Indonesia, Singapore, Vietnam, Laos, Cambodia, Thailand, the Philippines, Myanmar, and Brunei. Utilizing panel data from 1985 to 2021 for these ten ASEAN countries, the study employed both random effect and fixed effect models. The study presents two main findings: Firstly, it shows that education and purchasing power parity have a positive relationship with economic growth. Secondly, it identifies inflation as having a negative effect on economic development. This research highlights the importance of education in driving economic growth within ASEAN countries. Policymakers can benefit from these findings in formulating strategies to enhance education and mitigate inflation, thereby fostering economic development in the region.